Optimización del proceso de elaboración de malta de arroz (oryza sativa) - Romero Ibañez, Victor Hugo (2019)
This work aimed to optimize the process of making rice malt, for this the soaking time, concentration of NaOH% w / v and germination time were evaluated. For the experimental design, a DCCR and a response surface analysis were used, generating predictive models for the amount of ° brix and the germination percentage, obtaining an R2 of 0.8098 and 0.7682 respectively. For the germination percentage measurement, method 6.11.2.3 (NM-FF-043-SCFL-2003) was used and for the brix the musts were read that were macerated by a program developed with temperature changes and breaks. Optimum conditions were obtained with respect to the amount of ° brix with the parameters 60 hours (soak time), 0.08867 (NaOH concentration% w / v) and 62 hours (germination time). In addition, the optimal parameters were experimentally evaluated and the gelation temperatures of the malt were analyzed, as well as its viscosity and the reaction with iodine. The greatest extraction of soluble solids (° brix) that can be obtained during the maceration is above 50 hours of soaking and germination and for the germination percentages between 90 to 100% occur with a higher concentration of NaOH.